Exploring How Ontario Teachers Adapted to Learn-at-Home Initiatives During COVID-19 - Amanda Cooper; Kristy Timmons; Stephen MacGregor (University of Windsor, 2021)
At-home learning initiatives arose as a response to school closures due to COVID-19. This study interviewed 17 secondary teachers to explore the implementation of at-home learning in the province of Ontario, Canada. Findings suggest four thematic areas arising from the data: growing equity disparities, poor policy communication, factors influencing successful emergency remote teaching (technological and pedagogical), and impacts to academic and socio-emotional/mental health. This article proposes an integrated model for school recovery that will engage three levels of the education system: (1) school-level efforts including high-dosage tutoring and teacher collaboration and teacher looping strategies, (2) building partnerships with community organizations for wrap-around support for the most marginalized communities, and (3) parental engagement through actionable messages and tips by text to help parents support student learning. In the end, Ontario teachers rose to the challenge of providing students with consistent learning during the pandemic.